Dynamic removal of methylene blue and methyl orange from water using biochar derived from kitchen waste - Ghenwa Kataya; May Issa; Adnan Badran; David Cornu; Mikhael Bechelany; Salah Jellali; Mejdi Jeguirim; Akram Hijazi (Scientific Reports)
Abstract Access to pure and clean water is an upcoming challenge globally due to increased pollution by household waste and industrial effluents, specifically artificial dyes, which are not biodegradable and pose toxicity. Low-cost, mass-producible, and efficient technologies, particularly in developing environments, are highly needed. In this study, Kitchen waste derived biochar was prepared from orange peels (OP), potato peels (PP), banana peels (BP), and coffee residue (CR) via pyrolysis in a muffle furnace at 400 °C for 1 h. The prepared biochar was characterized by BET surface area analysis and Fourier Transform Infrared spectroscopy (FTIR). Low-cost kitchen waste derived biochar (KWDB)-sand composite filter material was developed as an eco-friendly adsorbent for the removal of a cationic Methylene Blue (MB) and an anionic dye Methyl Orange (MO) from aqueous solutions . Systematic research on contact time (0.5 to 24 h) and initial dye concentration (5–25 mg/L for MO and 10–180 mg/L for MB) was conducted. KWDB had extremely high and constant removal efficiency of a maximum of 99.5% for MB, while removal of MO was contact time dependent and had the following highest removal of 29% after 24 h. Higher initial dye concentration resulted in greater adsorption capacities. Langmuir isotherm analysis gave maximum adsorption capacities of 25.15 mg/g for MO and 30.40 mg/g for MB, which are greater than for most of the other biochars. Isotherm modeling further revealed that MO adsorption would be according to a multilayer, heterogeneous mode and MB adsorption according to a monolayer mode. This biochar-based filter is an efficient and scalable treatment system for water, particularly in situations with limited infrastructure, in which locally produced filters can be quickly implemented as part of inexpensive decentralized treatment systems. These findings confirm the design of biochar-enhanced filtration modules tailored for specific dye pollutants and environmental settings.